2022
DOI: 10.1177/02654075221127863
|View full text |Cite
|
Sign up to set email alerts
|

Sibling estrangement in adulthood

Abstract: Whereas interest in adult sibling relationships has been growing, we are not aware of any quantitative studies focusing on sibling estrangement (that is, lack of contact or emotional closeness). This gap in the literature seems unfortunate, because estrangement in close family relationships has been suggested to be momentous for family functioning and individuals’ well-being. Drawing on four waves of the German Family Panel (pairfam; n = 5,729), covering a 6-year observation period, we therefore assess respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…33 Siblings can and often do become alienated, especially in late adulthood. 34 Without a close relationship and a comprehensive understanding of their relative's condition, siblings of people with SMI may feel reluctant or resistant to provide support. Additionally, misconceptions, stigma and shame surrounding mental illness may lead to an avoidance of regular interaction with a relative with SMI, or at least restrict their ability to provide meaningful support.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Siblings can and often do become alienated, especially in late adulthood. 34 Without a close relationship and a comprehensive understanding of their relative's condition, siblings of people with SMI may feel reluctant or resistant to provide support. Additionally, misconceptions, stigma and shame surrounding mental illness may lead to an avoidance of regular interaction with a relative with SMI, or at least restrict their ability to provide meaningful support.…”
Section: Open Accessmentioning
confidence: 99%
“…Recent research also highlighted that sibling relationships are not necessarily enduring, meaningful or supportive throughout one’s life 33. Siblings can and often do become alienated, especially in late adulthood 34. Without a close relationship and a comprehensive understanding of their relative’s condition, siblings of people with SMI may feel reluctant or resistant to provide support.…”
Section: Introductionmentioning
confidence: 99%
“…Later in life, siblings are more likely to be sources of support for individuals who are single, widowed, and childless, especially when they live geographically close to each other (Campbell et al, 1999). While encountering disruptive or adverse family events can make sibling relationships more vulnerable and estranged (Hank & Steinbach, 2022), it has also been suggested that siblings' contact regularity increases after parental death (Kalmijn & Leopold, 2019). Altogether, sibling relationships are marked with both changes and stability, characterized by closeness, turbulence, estrangement, and reunion across life courses.…”
Section: Setting the Scene: Importance Of Sibling Tiesmentioning
confidence: 99%